Association between human olfactory performance and ability to detect single compounds in complex chemical mixtures - Sollai, Giorgia; Tomassini Barbarossa, Iole; Usai, Paolo; Hummel, Thomas; Crnjar, Roberto (Physiology & behavior, 2020)
•The number of odor-active compounds smelled is related to the olfactory threshold.•Intensity of complex banana odor is related to the number of banana-molecules smelled.•Intensity and pleasantness of the banana odor mixture are positively related.•Intensity of complex banana odor is related to that of isoamyl acetate. Humans can accurately discern thousands of odorants, although there is a considerable inter-individual variability. Individuals can be classified as normosmic, hyposmic or anosmic, depending on their olfactory sensitivity or blindness. In this research we studied the olfactory sensitivity to banana head-space as a complex odor mixture in a group of 53 subjects classified for their olfactory status, by means of the "Sniffin' Sticks" extended test. Using the coupled Gas Chromatography-Mass Spectrometry/ Olfactometry (GC–MS/O) technique, the single components of the banana flavor mixture were separated, identified and verbally evaluated by each subject. For each compound both the “odor type” (i.e., odor quality: fruity, floral, green, etc.) and “odor descriptor” (i.e., name used by subjects for odor identification) were reported, so that we could identify molecules that were defined as smelling of banana. The results show that: (a) the threshold olfactory performance is linearly correlated with the number of odor-active compounds (total or smelling of banana) for each subject; (b) the intensity reported by each subject during the sniffing of the pen containing the banana aroma in the identification test is positively correlated both with its hedonic valence and the number of odor-active compounds smelling of banana. In conclusion, our findings show that human perception of single compounds is conditioned by the threshold olfactory performance of the subject and that his/her ability to detect single molecular components, which smell as the mixture, affects the intensity and hedonism for the complex aroma.